Study on Protection and Development of County Traditional Villages Group from the Perspective of All-for-one Tourism in the New Period - Cai Pengcheng; Ubong Imang (RMP Publications, 2023)
Traditional villages are the historical memory of the Chinese nation, the essence of China's farming civilization, and also important historical and cultural heritage and tourism resources. Scholars at home and abroad have conducted in-depth research on the protection and development of traditional villages from various angles, but these studies lack the direction of traditional villages group in regional counties. The development of all-for-one tourism is a new concept and model for the protection and development of traditional villages in the new era. This paper attempts to apply the theory of all-for-one tourism to explore the path of protection and development of traditional villages group in the county. Traditional villages group in Tongjiang County, Sichuan Province were selected as the research area, and analyzed from the aspects of elements of traditional village cultural resources, opportunities and difficulties of protection and development, etc. Based on data analysis, a series of regional protection and development paths were proposed, including seizing policy opportunities, improving the special planning of all-for-one tourism, deeply strengthening the integration of agriculture, culture and tourism, mining the cultural connotation of villages, and cultivating villagers' main consciousness, are proposed to realize the sustainable development of the traditional village groups in the county.